The Relationship of Job Satisfaction and Human Resource Factors Towards Employees of Permodalan Nasional Berhad - Moonier, Khairul Razak (2012)
This study is to investigate the human factors that contribute to job satisfaction among employees in the Pemodalan Nasional Berhad (PNB), particularly at headquaters, Kuala Lumpur. It has five main objectives. The first objective of this study was to determine the level of job satisfaction by employees of PNR. The second objective was to identify current job function relationship of job satisfaction among employees of PNB. While the third objective is to distinguish between coaching and mentoring relationship with job satisfaction among employees of PNB. 'The fourth objective is to distinguish the relationship of compensation and payment of salaries by job satisfaction among employees of PNB.The objective of the fifth to distinguish the relationship of career development and opportunities in companies with job satisfaction among employees of PNB. The study also shows that in general staff job satisfaction PNB has a very good level.Among the factors that provide job satisfaction among employees of PNB is a function of the current work, kujuru1atihan and coaching, compensation and payment of salaries and career development and opportunities within the company. In this study. the reliability of test respondents using Cronbach Alpha test.The results showed that the rate of job satisfaction among employees of PNB is very good at reading 0.866.